Cost per response/remission in biologics available in Italy for the treatment of TNF-α inhibitors-naïve patients with ulcerative colitis. (January 2019) - Ruggeri, Matteo; Rolli, Francesca Romana
Objective: This study compares the cost of a sustained response or remission (at 52 weeks' follow-up) across biologics approved in Italy for the treatment of moderately to severely active ulcerative colitis (UC), specifically among anti-TNF-α-naïve patients. The analysis is from the perspective of the national healthcare provider (SSN) for one year of treatment. Methods: Efficacy data about the induction of response/remission probabilities at 52 weeks and the number needed to treat (NNT) were derived from a network meta-analysis of randomized controlled clinical trials of the following drugs: infliximab (originator and biosimilar), adalimumab, golimumab and vedolizumab. It included the acquisition and administration costs of biologics, based on an activity-based costing analysis performed in 3 Italian centers of excellence for UC treatment. Results: The costs per patient in sustained response at 52 weeks were, in increasing order: vedolizumab €47, 772 (95% CI €29, 869 - €101, 055), biosimilar infliximab €48, 657 (95% CI €31, 488 - €95, 523), golimumab (100 mg every 4 weeks at maintenance) €57, 940 (95% CI €38, 00 - €106, 206), golimumab (50 mg every 4 weeks at maintenance) €62, 504 (95% CI €39, 976 - €120, 477), adalimumab €101, 181 (95% CI €49, 635 - €422, 334). The costs per patient in sustained remission at 52 weeks were: vedolizumab €86, 220 (95% CI €47, 015 - €206, 652), biosimilar infliximab €92, 562 (95% CI €52, 954 - €203, 619). Conclusions: In patients with moderate to severe UC not previously treated with TNF-α inhibitors, treatment needed with vedolizumab to obtain a response or remission at 52 weeks of follow-up is less costly to the SSN compared with the other UC-approved biologics available in Italy.